Para além da produtividade econômica: um estudo acerca das condicionantes da função social da propriedade rural - Melo, Alexandre Campos (2013)
This research promotes an analysis of the social function of land ownership in Brazilian law. It argues that the concept of the social function of rural property is contained in the concept of productivity, but can not be without this social function, so that the term "productive property" contained in Art. 185, item II of the Constitution of 1988, is related to both economic and social aspects. It can be deducted from the systematic interpretation of Articles 185 and 186 of the Constitution, in line with the program constitutional under Articles 1, 3 and 170 of the Charter, through which is promoted the true meaning of the multidimensionality of the social function of rural property. So, the elements of the social function of landownership - the economic (rational and appropriate use), the environmental (appropriate use of natural resources and preservation of the environment) and social (observance of the rules that regulate labor relations and exploration that favors the welfare of owners and workers) - integrate the concept of productivity, so that it is at the same time, container and content of the social function of property.